Cochrane Review: There is no evidence for the effectiveness of baclofen in alcoholic addiction - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
Cochrane systematic review couldn’t find evidence of the effectiveness of baclofen in alcohol dependence for abstinence syndrome.